2017
DOI: 10.11648/j.jddmc.20170306.11
|View full text |Cite
|
Sign up to set email alerts
|

Naproxen-Gelucire Nanoformulations for Improved Solubility and Dissolution Rate of Poorly Water-Soluble Drug Naproxen

Abstract: Naproxen-Gelucire Nanoformulations (NFs) in terms of their phase solubility behavior, physico-chemical characteristics, cytotoxicity and morphology and dissolution enhancement has been studied using the poorly water soluble drug, naproxen. The NFs were prepared via wet milling using a conventional Retsch Planetary ball mill in various ratios of drug to polymer (1:1, 1:2, 1:3, 1:4). The release rate of naproxen from various ratios of drug/polymer nanoparticles was investigated using USP paddle apparatus (type I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…the physicochemical characteristics, brain penetration properties and dosage of the drugs. Conventional analgesic NSAIDs include acetylsalicylic acid (ASA), mefenamic acid (MEF), and naproxen (NAP) , . NSAIDs are widely administered against a wide range of inflammatory diseases to treat moderate pain including fever, headache, dental pain, postoperative and postpartum pain, dysmenorrhea, osteoarthritis, rheumatoid arthritis .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…the physicochemical characteristics, brain penetration properties and dosage of the drugs. Conventional analgesic NSAIDs include acetylsalicylic acid (ASA), mefenamic acid (MEF), and naproxen (NAP) , . NSAIDs are widely administered against a wide range of inflammatory diseases to treat moderate pain including fever, headache, dental pain, postoperative and postpartum pain, dysmenorrhea, osteoarthritis, rheumatoid arthritis .…”
Section: Introductionmentioning
confidence: 99%
“…Conventional analgesic NSAIDs include acetylsalicylic acid (ASA), mefenamic acid (MEF), and naproxen (NAP) , . NSAIDs are widely administered against a wide range of inflammatory diseases to treat moderate pain including fever, headache, dental pain, postoperative and postpartum pain, dysmenorrhea, osteoarthritis, rheumatoid arthritis . However, NSAIDs are accompanied with limitations such as lack of specificity toward desired tissues, high distribution volume, lack of selectivity, poor aqueous solubility and dissolution rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the coexistence of hydrophilic carriers like Gelurice ® 48/16 may decrease the hydrophobicity of the drug particle surfaces, which will subsequently increase interaction with the aqueous medium and boost the rate of CXB’s dissolution [ 7 ]. Several previous studies showed the enhanced release performance exhibited after the addition of Gelurice ® 48/16 [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%